Impact of cement-augmented condylar screws in locking plate osteosynthesis for distal femoral fractures — A biomechanical analysis. Issue 12 (December 2016) - Bliemel, Christopher; Oberkircher, Ludwig; Bockmann, Benjamin; Petzold, Eric; Aigner, Rene; Heyse, Thomas Jan; Ruchholtz, Steffen; Buecking, Benjamin
Abstract: Introduction: Compromised bone quality and the need for early mobilization continue to lead to implant failure in elderly patients with distal femoral fractures. The cement augmentation of screws might facilitate improving implant anchorage. The aim of this study was to analyse the impact of cement augmentation of the condylar screws on implant fixation in a human cadaveric bone model. Material and methods: Ten pairs of osteoporotic femora (mean age: 90 years, range: 84–99 years) were used. A 2-cm gap osteotomy was created in the metaphyseal region to simulate an unstable AO/OTA 33-A3 fracture. All specimens were treated with a polyaxial locking plate. Specimens randomly assigned to the augmented group received an additional cement augmentation of the condylar screws using bone cement. A servohydraulic testing machine was used to perform incremental cyclic axial loading using a load-to-failure mode. Results: All specimens survived at least 800 N of axial compressive force. The mean compressive forces leading to failure were 1620 N (95% CI: 1382–1858 N) in the non-augmented group and 2420 N (95% CI: 2054–2786 N) in the group with cement-augmented condylar screws ( p = 0.005). Deformation with cutting out of the condylar screws and condylar fracture were the most common reasons for failure in both groups. Whereas axial stiffness was comparable between both osteosyntheses ( p = 0.508), significant differences were observed for the plastic deformation of the constructs ( p = 0.014). Conclusion: The results of the present study showed that the cement augmentation of the condylar screws might be a promising technique for the fixation of distal femoral fractures in elderly patients with osteoporotic bones.